Numerical Estimation of Settlement under a Shallow Foundation by the Pressuremeter Method - Ouabel, Houari; Zadjaoui, Abdeldjalil; Bendiouis-Benchouk, Assia (Salehan Institute of Higher Education, 2020)
This work has two axes: The first one is theoretical (bibliographic analysis) on the theoretical estimation of the settlement under a Shallow foundation with the contribution of the characteristics of the results of the pressurometric tests and the second numerical axis by the numerical evaluation of the settlement generated by a superficial foundation that always happens by estimating the carrying capacity of these foundations by two methods the first is the classical method and the second the empirical method based on the direct interpretation of the in situ test such as the pressuremeter test by the determination Pressuremeter characteristics (Limit pressure (Pl) and Â the Pressuremeter module (EM)), our contribution consists in using a calculation code based on the finite element method with the contribution of two laws of elastoplastic behavior namely Mohr-Coulomb and Cam- Clay we use geotechnical Â survey results project of the railway line project (Tissemesilt-Alger-Bughazoul) in Algeria.